IMPLEMENTATION OF MAYOR REGULATION NO. 16 2011 ABOUT TRAFFIC CONTROL ZONE IN MEDAN CITY - Ningsih, Suria; Agusmidah (International Journal of Psychosocial Rehabilitation, 2020)
The implementation of a Traffic Control Zone aims to overcome traffic congestion in Medan so that the people of Medan can ride comfortably and safely. This research was conducted to see the implementation of the regulation of traffic order in Medan through Medan Mayor Regulation No.16 2011 about the Traffic Control Zone. This type of research is empirical juridical conducted with 2 stages, namely the first stage of the study of normative law and the second stage of the study of the implementation of regulations by collecting secondary data through literature studies and primary data through questionnaires, interviews and FGD. The results showed the Traffic Control Zone was formed on the protocol roads in Medan City. In this area, it is determined what are the obligations, prohibitions and sanctions. For its supervision, the Transportation Office, Medan Police Traffic Unit, and the Medan City Police Task Force were appointed. The policies implemented by the Medan City Government in traffic-regulated areas are the installation of road equipment in the form of installing traffic signs, road markings and ATCS on traffic light, pedestrian improvements prioritizing pedestrians, making TCZ a pilot area for the implementation of Integrated Urban Road Safety, applying maximum fines at TCZ if a traffic violation occurs.